2010
DOI: 10.1007/s10551-010-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Relational Consequences of Perceived Deception in Online Shopping: The Moderating Roles of Type of Product, Consumer’s Attitude Toward the Internet and Consumer’s Demographics

Abstract: perceived online deception, consumer satisfaction, loyalty intentions, type of products, moderating effects,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 75 publications
11
111
1
3
Order By: Relevance
“…There are many studies in the literature addressing various issues concerning marketing ethics [22,23,24]. However, previous researchers have tended to ignore other potential important ethical marketing issues pertaining to the internet, such as deception, dishonesty, and accuracy [25]. Though the CPEOR scale was developed in 2007, few studies e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many studies in the literature addressing various issues concerning marketing ethics [22,23,24]. However, previous researchers have tended to ignore other potential important ethical marketing issues pertaining to the internet, such as deception, dishonesty, and accuracy [25]. Though the CPEOR scale was developed in 2007, few studies e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust perception include the fact the financial service provider would not take advantage of the vulnerability of the consumer regarding the terms and conditions of the loan. When a consumer realizes that he/she has been deceived by a loan service provider, it is likely to reduce the customer's confidence and trust perception for the loan service provider (Román, 2010;Romani, 2006). This, therefore, leads to the hypothesis that:…”
Section: Perceived Deception and Trustmentioning
confidence: 99%
“…Moreover, existing studies have established that deception can influence sales volume, evaluation of product attributes (Estrada, 2006;Newell, Goldsmith, & Banzhaf, 1998) and other consumer behaviour such as attitude towards advertising (Chaouachi, et al, 2012) and consumer loyalty to service providers (Limbu, Wolf, & Lunsford, ISSN 1923-4023 E-ISSN 1923 2011; Román, 2010). There is void in the extant literature regarding evidence of the antecedents and effects of CPD on consumer behaviour such as trust, satisfaction and behavioural intentions for service providers, especially in financial service context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristically, when customers feel that they are not getting the best value for their money, they will begin searching for alternatives, which means that their loyalty declines dramatically. The association between perceived value and customers' loyalty/intention to purchase or repurchase has been proven to be positive in many studies [48,212,213,223]. Luarn and Lin [122] investigated the main antecedent influences on loyalty for the eservice context in a sample of 180 customers and found that perceived value is associated with loyalty both positively and directly (β=0.230, p<0.001).…”
Section: Perceived Valuementioning
confidence: 99%